(untitled) (Research, Society and Development, 2020)
The ornamentation of social spaces provides its users with several benefits in the community, especially the beautification of these spaces, making them more pleasant and useful. This work aimed to develop actions related to Environmental Education through landscaping practices and landscaping of social spaces of rural communities. Valuing the culture and preservation of the vegetation of these spaces, through workshops, which took place together with the City Hall and EMATER/RS-ASCAR Regional of Faxinal do Soturno, RS, in two moments: morning and afternoon. The morning was devoted to the theoretical part and the afternoon to the practical part. There was a good receptivity on the theme addressed during the workshop, both in the theoretical part with technical exposure and debate about the importance of the environment and living spaces, as well as in the practical part with great participation in the design and implementation of the landscaping of the chosen spaces. It was found that the interdisciplinarity characteristic of Environmental Education makes possible, in our work, the practices of landscaping and gardening, to awaken the awareness of the participants about the importance of the environment, regardless of the size and scope of social spaces for social interaction, a good quality of life.